Investigation of dual electromagnetically induced grating based on spatial modulation in quantum well nanostructures via biexciton coherence. (17th February 2017) - Naseri, Tayebeh
Abstract: A new scheme for obtaining an electromagnetically induced grating (EIG) via biexciton coherence in quantum well nanostructures is developed. It is theoretically shown that exciton spin relaxation and biexciton binding energy have important roles in producing efficient dual electromagnetically induced phase grating. In this structure, due to biexciton coherence, the higher order diffraction intensities of the grating can be observed. Furthermore, it is shown that the efficiency of different orders in the grating patterns could be controlled by biexciton energy renormalization (ESR) and relative phase between the applied laser fields.